Lazer noturno LGBTQIAPN+ em Araraquara e São Carlos: sociabilidades não hegemônicas no interior - Santos, Mateus Rodrigues dos (2024)
Research on LGBTQIAPN+ sociability may be common in metropolitan contexts, but dealing with municipalities such as Araraquara and São Carlos - SP, which are often seen as medium-sized cities and inland cities, is new, as it moves into a little-explored empirical context, draws attention to the diversities of Brazilian interiors and medium sized cities, problematizing these notions and stereotypes often directed at these regions. This work begins along these lines, presenting the relationship between the city, dissident sexualities and sociability in anthropology in an intertwined way, and goes on to include Araraquara and São Carlos as another urban dimension that can be reflected on, especially from the perspective and experiences of non-heterosexual cis. The bars, nightclubs and events ethnographed have their own attractive and structural characteristics that have an impact on the urban landscape of both cities by becoming points of reference for LGBTQIAPN+ residents. At the parties, the processes of sociability are marked by rapprochement, links, disputes and distancing, produced by other social markers besides gender and sexuality, seen as the starting point that brings them together, as well as by the intense performativity of the conduct and bodily presentations of those present. In addition, elements such as the musical environment and alcohol consumption also drive and complexify relationships. The result is the production of phenomena that sometimes generate differentiations and similarities between Araraquara and São Carlos, and sometimes between the two in relation to larger urban centers, demonstrating the potential of ethnography to recognize diversity and the way people manage themselves situationally, the influence of everyday life on identities and their flexible and changeable capacity.